Intranasal Application of Lactococcus lactis W136 Is Safe in Chronic Rhinosinusitis Patients With Previous Sinus Surgery - Endam, Leandra Mfuna; Alromaih, Saud; Gonzalez, Emmanuel; Madrenas, Joaquin; Cousineau, Benoit; Renteria, Axel E.; Desrosiers, Martin (Frontiers in Cellular and Infection Microbiology, 2020)
Objective: Modulation of the dysbiotic gut microbiome with 'healthy' bacteria via a stool transplant or supplementation is increasingly practiscd, however this approach has not been explored in the nasal passages. We wished to verify whether Lactococcus lactis W136 (L. lactis W136) bacteria could be safely applied via irrigation to the nasal and sinus passages in individuals with chronic rhinosinusitis (CRS) with previous undergone endoscopic sinus surgery, and whether this was accompanied by bacterial community flora modification. Study Design: Prospective open-label pilot trial of safety and feasibility. Setting: Academic tertiary hospital centre Subjects and Methods: Twenty-four patients with CRS refractory to previous medical and surgical therapy received a 14-day course of BID sinus irrigations containing 1.2 x 109 CFU live L. lactis W136. Patients were monitored for safety using questionnaire, sinus endoscopy, otoscopy, UPSIT-40 smell testing, and endoscopically-obtained sinus culture. Assessors were blinded as to treatment phase. Physician assessors were blinded to treatment stage. Results: All 24 patients receiving at least one treatment successfully completed treatment. L. lactis W136 probiotic treatment was safe, with no major adverse events or new infections. Treatment was associated with improvement in sinus symptoms, QOL, and mucosal scores, which remained improved during the subsequent 14-day observation period. Microbiome changes associated with treatment were limited to an increase of the pathobiont Dolosigranulum Pigrum, a potential novel pathobiont. Subgroup analysis suggested differences in microbiomes and responses for CRSsNP and CRSwNP phenotypes. Conclusion: Intranasal irrigation of live L. lactis W136 bacteria to patients with refractory chronic rhinosinusitis was safe, and was associated with effects on symptoms, mucosal aspect and microbiome composition. Intranasal bacteria may thus find a role as a treatment strategy for CRS. Clinicaltrials.gov identifier: NCT04048174. Funding: McGill Faculty of Medicine Grant